POLICY-LEGAL INSTRUMENTS OF INDIRECT ENVIRONMENTAL MANAGEMENT - Jelena Šogorov Vučković (Srpska Politička Misao)
Effective environmental protection cannot be imagined without direct management of such protection by state authorities through legal prohibitions and orders, permits, approvals and exemptions, mandatory notifications, control, and repression measures of the state administration, etc. Yet, in modern environmental systems, instruments of indirect influence on the addressees of norms are gaining increasing importance, with the aim of influencing their desirable behaviour through citizens’ awareness. Such instruments are used by law primarily in the field of prevention, with the aim of preventing environmental damage. When using indirect means, the state appeals to the addressees to act appropriately to protect the environment, but without forcibly sanctioning behaviour, if that appeals are not accepted. This paper analyses the nature of indirect instruments, such as public information, economic incentives of the classical and modern types, as well as environmental agreements, with an indication of their role and importance in modern environmental systems.